Electroconvulsive therapy portrayal in contemporary video games - Buday, Jozef; Neumann, Miroslav; Žaludová Heidingerová, Jana; Mareš, Tadeáš; Magyarová, Eva; Thai Le, Hong; Divácký, Daniel; Jirečková, Gabriela; Albrecht, Jakub; Kališová, Lucie; Pol, Marek; Mahrík, Jakub; et al. (Frontiers in Psychiatry, 2024)
Electroconvulsive therapy (ECT) is an important treatment modality in psychiatry, considered to be the most effective option for pharmaco-resistant affective and psychotic disorders. Despite its great efficacy, it still remains a rather controversial method, which hinders its full potential. It is feasible to say that in part, this controversy is caused by a largely negative image of ECT displayed through media. The depiction of ECT in movies has been studied and well documented in the past. The aim of our study was to provide an overview of how ECT is represented in video games - a form of media where ECT representation has been overlooked in scientific literature so far. As with movies, most of these portrayals are negative, depicting ECT as an obsolete, aggressive or torturous treatment method.